Hand hygiene in health care: 20 years of ongoing advances and perspectives. Issue 8 (August 2021) - Lotfinejad, Nasim; Peters, Alexandra; Tartari, Ermira; Fankhauser-Rodriguez, Carolina; Pires, Daniela; Pittet, Didier
Summary: Health-care-associated infections are the most prevalent adverse events of hospital care, posing a substantial threat to patient safety and burden on society. Hand hygiene with alcohol-based hand rub is the most effective preventive strategy to reduce health-care-associated infections. Over the past two decades, various interventions have been introduced and studied to improve hand hygiene compliance among health-care workers. The global implementation of the WHO multimodal hand hygiene improvement strategy and constant efforts to replace the use of soap and water with alcohol-based hand rub have led to a faster and more efficient hand cleaning method. These strategies have strongly contributed to the success of behaviour change and a subsequent decrease in health-care-associated infections and cross-transmission of multidrug-resistant organisms worldwide. The WHO multimodal behaviour change strategy requires a series of elements including system change as a prerequisite for behaviour change, education, monitoring and performance feedback, reminders in the workplace, and an institutional safety climate. Successful adoption of the promotion strategy requires adaptation to available resources and sociocultural contexts. This Review focuses on the major advances and challenges in hand hygiene research and practices in the past 20 years and sets out various ways forward for improving this lifesaving action.